Modeling and Simulation of Pore Morphology Modifications using Laser-Structured Graphite Anodes in Lithium-Ion Batteries. Issue 1 (1st January 2020) - Kraft, Ludwig; Habedank, Jan B.; Frank, Alexander; Rheinfeld, Alexander; Jossen, Andreas
Abstract : The energy density of lithium-ion batteries can be enhanced by using thicker and denser electrodes, which leads to transport limitations in the electrolyte within the porous structures. A pore morphology modification of the electrodes can counteract this limitation mechanism and provide higher rate capabilities of the cells. In this work, graphite anodes are structured with a picosecond laser in order to create transport pathways for the lithium-ions and allow for enhanced penetration of the electrodes. Experimental data from graphite/NMC-111 coin cells with varying areal capacities are used for the development and parameterization of an electrochemical model. The modified pore morphology of the structured electrodes is represented in the model by an adapted tortuosity, which results in lower lithium-ion concentration gradients and reduced diffusion polarization in the electrolyte. The effect of electrode thickness and tortuosity on limiting mechanisms is analyzed via simulation studies in order to derive the impact of structured electrodes. As a result, improved discharge as well as charge rate capability appears beside enhanced safety features such as increased tolerance versus hazardous lithium-plating during fast charging scenarios.